Spring-loaded body mass equivalent horizontal reactive countermovement jump ground contact and flight times, but not peak forces, are comparable to vertical jumping - Jones, E. J.; Kennett, J. E.; Green, D. A. (Journal of Biomechanics, 2021)
Horizontal (cylinder-based) sledge jumping has been shown to ameliorate multi-system deconditioning induced by long-term bed-rest. However, biomechanics differ from 1 g vertical jumping, in particular prolongation of ground contact times (GCT), reduction of peak force, rate of force development (RFD) (and presumably stretch shortening cycle [SSC] efficacy) and stiffness, whilst also requiring relatively complex equipment. Thus, we sought to determine if horizontal spring-loaded countermovement jumps were more analogous to vertical jumping.